Big sky - Atkinson, Kate (New York Little, Brown and Company, 2019)
Jackson Brodie has relocated to a quiet seaside village, in the occasional company of his recalcitrant teenage son and an aging Labrador, both at the discretion of his ex-partner Julia. It's picturesque, but there's something darker lurking behind the scenes. Jackson's current job, gathering proof of an unfaithful husband for his suspicious wife, is fairly standard-issue, but a chance encounter with a desperate man on a crumbling cliff leads him into a sinister network - and back across the path of his old friend Reggie.
107207
Keywords: Brodie, Jackson (Fictitious character) -- Fiction; Private investigators -- Fiction; Villages -- Fiction; Human trafficking -- Fiction; Detective and mystery fiction; Thrillers (Fiction); Mystery fiction; Fiction; Suspense fiction